IMPLEMENTATION ACTIONSCRIPT 3 IN MAKING MULTIPLATFORM APPLICATIONS TO RECOGNIZE PREPARATION FOR EARTHQUAKE - Wijaya, Rian Farta; Putri, Ataya; Hermansyah, Hermansyah; Mayasari, Nova; Hardinata, Rio Septian (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Indonesia is an archipelagic country which is geographically located at the confluence of four tectonic plates, namely the Indo-Australian, Eurasian, Pacific and Philippine plates. Thus, causing Indonesia to have a volcanic belt in the form of volcanic mountains. Indonesia is one of the countries that has the highest level of seismicity in the world. The purpose of this research is to apply ActionScript 3 in the manufacture of multi-platform applications to identify preparations for earthquakes that can add insight to users in dealing with earthquake disasters, as a learning aid for children aged 8 to 12 years. This application was created using Adobe Flash Professional CS 6, ActionScript 3 as a programming language and Adobe Audition CS 6. It is hoped that with this application, users will be able to recognize earthquake learning. From the results of the study, it can be concluded that this multiplatform application to recognize preparation for earthquakes has been successfully created which consists of 5 menus on the main menu, namely, about earthquakes, before, during, after earthquakes and quizzes. Keywords: ActionScript, Adobe Flash Professional CS6, Application, Multiplatform